2016
DOI: 10.1111/pedi.12370
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in type 1 diabetes

Abstract: Environmental factors play an important role in the pathogenesis of type 1 diabetes and can determine if a genetically susceptible individual develops the disease. Increasing evidence suggest that among other exogenous agents certain virus infections can contribute to the beta-cell damaging process. Possible viral etiology of type 1 diabetes has been explored extensively but the final proof for causality is still lacking. Currently, the group of enteroviruses (EVs) is considered as the strongest candidate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 63 publications
0
102
0
1
Order By: Relevance
“…Earlier studies also reported aberrant expression of HLA-II molecules by β cells in 22 of 26 and 6 of 12 pancreata from patients with recent-onset and long-standing disease, respectively (25,27,28). Expression of HLA-I/II molecules may be triggered by viruses linked to T1D (29,30). Inflammatory cytokines (IFN-γ plus TNF-α or lymphotoxin) induce HLA-I/II molecules on β cells in vitro (31,32).…”
Section: T Cells In the Prediabetic Pancreasmentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier studies also reported aberrant expression of HLA-II molecules by β cells in 22 of 26 and 6 of 12 pancreata from patients with recent-onset and long-standing disease, respectively (25,27,28). Expression of HLA-I/II molecules may be triggered by viruses linked to T1D (29,30). Inflammatory cytokines (IFN-γ plus TNF-α or lymphotoxin) induce HLA-I/II molecules on β cells in vitro (31,32).…”
Section: T Cells In the Prediabetic Pancreasmentioning
confidence: 92%
“…Along with their epidemiological associations (29,30), enterovirus infections of β cells impair insulin secretion (118), alter mRNA/miRNA expression (119,120), and induce interferon responses (121,122) that promote β cell stress, dysfunction, and apoptosis (123). Enteroviruses may also trigger autoimmunity via presentation of self-molecules in an inflammatory context (bystander activation) (124) and/or by molecular mimicry (125)(126)(127).…”
Section: Modified T Cell Autoantigens (Neoepitopes)mentioning
confidence: 99%
“…4 Prospective studies confirmed the link between EV and the development of pancreas islet autoimmunity. 5 Moreover, experimental studies, in vitro and in vivo animal models, revealed that CV-B4 may be involved in the pathogenesis of T1D through several mechanisms. 2,6,7,8 It has been shown that non-neutralizing anti-CV-B4 IgG obtained from serum of patients can increase the infection of peripheral blood mononuclear cells (PBMC) with CV-B4, which results in production of IFNa and other inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and research findings indicate an association between enterovirus infection and the onset of autoimmunity against β cells in T1D [9]. IFIH1 encodes melanoma differentiation-associated protein 5 (MDA5), a sensor of double-stranded RNA that initiates the innate immune response against infections by RNA viruses.…”
Section: Introductionmentioning
confidence: 99%